A Smart Route for Encapsulating Pd Nanoparticles into a ZIF-8 Hollow Microsphere and Their Superior Catalytic Properties - Zhao, Yaqian (Langmuir : the ACS journal of surfaces and colloids, 2020)
The encapsulation of catalytically active noble metal nanoparticles (NM NPs) into metal-organic frameworks (MOFs) represents an effective strategy for enhancing their catalytic performance. Despite a myriad of reports on the nanocomposites consisting of NM NPs and MOFs, it remains challenging to develop a sustainable and convenient method for realizing confined integration of NM NPs within a porous and hollow zinc-based MOF. Herein, a simple and well-designed approach is reported to the fabrication of PdZIF-8 hollow microspheres with a number of Pd nanoparticles immobilized on the inner surface. This method capitalized on the use of polyvinylpyrrolidone (PVP)-stabilized polystyrene (PS) microspheres as templates, to harness the dual functions of PVP for reducing PdCl2 to generate Pd NPs and coordinating with zinc ions to grow ZIF-8 shells. Consequently, it avoids the complicated protocols involving surface treatment of template microspheres that conventionally adopts hazardous or costly agents. The obtained Pd@ZIF-8 hollow microspheres exhibit outstanding catalytic activity, size selectivity, and stability in the hydrogenation of alkenes. This study presents both the advances in the green synthesis and great potential of Pd@ZIF-8 hollow microspheres for catalytic applications